Word Expressions of Agreement and Disagreement Used by The Students in Speaking Class (A Study at English Education Study Program of STKIP PGRI Sumatera Barat) - Muhammad Khairi Ikhsan (English Education Journal, 2019)
This research is aimed at investigating word expressions of agreement and disagreement during group discussion activities in speaking class at English Education Department of STKIP PGRI Sumatera Barat. The word expressions were classified based on classification proposed by Rizvi (2005, p. 185). The classifications were strong and neutral (agreements and disagreements). The researcher used purposive sampling to answer the research questions. The researcher chose the students who expressed word expressions of agreement and disagreement in stating the opinion. In collecting the data the researcher did observation for each class by using observation checklist, field note and video recorder as instruments. The data were collected by the researcher and classified into the classifications. There were thirty five (35) students of English Education Department of STKIP PGRI Sumatera Barat who used word expressions of agreements and disagreements in stating their opinion in group discussion activities in speaking class. Thus, the two classifications of agreements and disagreements were variously  found in the students’ expressions.